Uzbekistan: The Emerging Hub for Foreign Investment in Central Asia - Akishova, Shaxnoza (Innovative Technologica: Methodical Research Journal, 2025)
Situated in the core of Central Asia, Uzbekistan has become an energetic center for foreign investment, propelled by extensive economic reforms, open market policies, and improved regional links. Since 2016, the government has taken significant steps to liberalize its economy, which include freeing currency controls, privatizing state enterprises, and establishing special economic zones aimed at attracting international investors. With a population exceeding 36 million, a youthful and expanding labor force, along with a wealth of natural resources, Uzbekistan presents considerable prospects in areas such as energy, agriculture, textiles, mining, and technology. The nation’s dedication to enhancing its business environment, paired with its critical involvement in China's Belt and Road Initiative and various transcontinental trade routes, positions it as a key entry point between Europe and Asia. This paper examines Uzbekistan's evolution into a prominent investment site, focusing on the primary forces driving its economic revival, the hurdles it must overcome, and the potential for ongoing growth amid the changing geopolitical dynamics of Central Asia. Through the analysis of successful foreign investment case studies and existing policy frameworks, this study underscores Uzbekistan's promise as a foundational element of economic progress in the region